Prolotherapy in the treatment of chronic migraine — Case report - Bernardo Souto, Ítallo; Santos de Lima, Fernanda Fabiola; Arapiraca Ferreira, Vanessa; Batista Lopes, Camila Emily; Lacerda Sousa, Laylla Gabrielly; Egypto Pereira, Victor; Severo Bem Junior, Luiz (Headache Medicine, 2023)
Introduction Chronic migraine is a socioeconomic and individual burden since it is the largest cause of disability in people under 50 years of age. Although there are several prophylactic drug alternatives, some patients are vulnerable to refractoriness with significant damage to their quality of life. Prolotherapy, a subcutaneous injection of dextrose in peripheral nerves, advocates as a promising tool in the management of this pathology. Case report A patient with refractory chronic migraine to drug therapy who was submitted to neurofascial prolotherapy. Weekly administration of a 2 ml solution of 1% ropivacaine and 10% glucose in the head peripheral nerves for 6 weeks. Reduced disability and frequency of migraine attacks for a period of 8 weeks after interventions. Conclusion Prolotherapy proved itself to be a notable technique for reducing the number of days in a month that a patient with refractory chronic migraine to standardized therapy has had headaches. However, placebo group studies are needed to determine the efficacy of the procedure.